Study on coal drawing parameters of deeply buried hard coal seams based on PFC - Li Xinlei; Ren Ziyuan; Cao Zhengzheng; Ren Hao (Scientific Reports)
Abstract The coal seams in the Zhaogu mining area are characterized by great burial depth, hard coal quality, and difficulty in fracturing the top coal. To address the challenges of top-coal drawing in the working face, this study focuses on the external coal pillar working face in the Second Panel. Through laboratory experiments, field tests, and PFC numerical simulations, the coal drawing parameters and top-coal caving techniques were systematically investigated to provide technical support for on-site production. Key findings include: (1) Borehole observations revealed that adjacent goaf mining activities induced stress redistribution toward deeper zones, promoting full fragmentation of top coal. (2) Numerical simulations demonstrated the significant influence of mining-to-drawing ratio (MDR) on top-coal failure characteristics, with optimal recovery rate (TCRR) achieved at 1:1 MDR. (3) Parameter analysis showed the lowest gangue content occurred at 0.8 m drawing step distance, while single-round multi-opening interval drawing strategy delivered superior economic benefits and higher recovery compared to traditional multi-round approaches. (4) Similarity simulation tests uncovered funnel interaction patterns between adjacent drawing openings, with peak efficiency during initial drawing phases and an overall simulated recovery rate of 86.23%. Field applications confirmed the method’s effectiveness, showing no significant fluctuations in support pressure during operation. The research results provide critical parameter optimization schemes and technical implementation pathways for efficient extraction of deep-buried hard coal seams under complex geological conditions.